2021
DOI: 10.1038/s41598-021-85849-4
|View full text |Cite|
|
Sign up to set email alerts
|

Potential zoonotic pathogens hosted by endangered bonobos

Abstract: Few publications, often limited to one specific pathogen, have studied bonobos (Pan paniscus), our closest living relatives, as possible reservoirs of certain human infectious agents. Here, 91 stool samples from semicaptive bonobos and bonobos reintroduced in the wild, in the Democratic Republic of the Congo, were screened for different infectious agents: viruses, bacteria and parasites. We showed the presence of potentially zoonotic viral, bacterial or parasitic agents in stool samples, sometimes coinfecting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 63 publications
0
14
0
Order By: Relevance
“…Human immunodeficiency virus infections markedly increase neopterin levels in humans (Fuchs et al, 1992), and a similar immune response is reported for macaques infected with the related simian immunodeficiency virus (SIV) (Higham et al, 2015). SIV infections are common and widespread in wild chimpanzees (Gao et al, 1999;Li et al, 2012), but no bonobo sample from the wild or sanctuary has tested positive for SIV (Li et al, 2012;Medkour et al, 2021). Therefore, low neopterin levels in wild bonobos could also reflect differences in SIV prevalence between these species.…”
Section: Neopterin Levels Are Independent Of Environmental Contextmentioning
confidence: 78%
“…Human immunodeficiency virus infections markedly increase neopterin levels in humans (Fuchs et al, 1992), and a similar immune response is reported for macaques infected with the related simian immunodeficiency virus (SIV) (Higham et al, 2015). SIV infections are common and widespread in wild chimpanzees (Gao et al, 1999;Li et al, 2012), but no bonobo sample from the wild or sanctuary has tested positive for SIV (Li et al, 2012;Medkour et al, 2021). Therefore, low neopterin levels in wild bonobos could also reflect differences in SIV prevalence between these species.…”
Section: Neopterin Levels Are Independent Of Environmental Contextmentioning
confidence: 78%
“…An epidemiologic study evaluating fecal samples of 91 bonobos ( Pan paniscus ) from 2 populations in a semi-captivity setting that were reintroduced into the wild at the DRC, showed no evidence of Mycobacterium spp. [ 52 ]. Fecal screening has low sensitivity because requires the mycobacteria to be excreted in feces, which only occurs during active infection.…”
Section: Discussionmentioning
confidence: 99%
“…The availability of various tools including suitable animal models to study HAdVs is particularly important as the adenoviruses are diversifying, and more and more cases of interspecies transmission pose the risk of zoonotic and anthroponotic spillover events [ 148 , 149 , 150 , 151 , 152 , 153 , 154 , 155 , 156 ]. Interesting and germane research questions that could be addressed using wild type and chimeric viruses in in vitro and in vivo studies include, but are certainly not limited to: What defines the host range of adenoviruses?…”
Section: Discussionmentioning
confidence: 99%